Intervening Effect of Cash Holdings in the Relationship Between Financial Performance and Dividend Policy - Geoffrey Mbuva Kimunduu; Mirie Mwangi; Erasmus Kaijage; Duncan Elly Ochieng (European Scientific Journal, ESJ, 2017)
Many studies on relationship between financial performance and dividend policy have resulted to controversial outcome with few studies questioning the intervening effect of cash holdings. The purpose of this study was to evaluate the effect of cash holdings on the relationship between financial performance and dividend policy. The study applied positivism research philosophy and descriptive causal research design. The study was anchored on hypothetical view that the relationship between financial performance and dividend policy of firms listed at the Nairobi securities exchange is not intervened by cash holdings which was tested against a sample size of 31 firms listed at the Nairobi securities exchange selected using purposive sampling technique. The research findings were as follows: There was a significant direct association between operating cash flows and dividend policy which was intervened by cash holdings. In general it was concluded that the link between financial performance and dividend policy of firms listed at the Nairobi securities exchange was significant. The study outcome augment existing knowledge on financial performance and dividend policy for it is evident that firms with ability to generate income directly influence dividend payout ratio and therefore, top management should enhance financial performance and not dividend policy which is irrelevant. Cash holdings intervenes this relationship hence the level of cash balances maintained by the firm explain more on the reason why some firms pay more dividend on increase of profitability levels while others does not. Regulatory bodies such as Capital Market Authority and Centre for Corporate Governance use these research findings to improve their financial viability assessment approach of firms listed at the Nairobi securities exchange.